Occupational Asthma Management (Actualité en allergologie et en immunologie au Canada, 2024)
Occupational asthma is defined as asthma that is caused by work exposures, accounting for approximately 10-15% of all new-onset adult asthma. Typically, this is a new-onset of asthma in workers with no previous history of asthma. However, the diagnosis may also be made in individuals who had previous childhood asthma that cleared, then recurred as an adult due to work exposure. In contrast, work-exacerbated asthma is defined as asthma that is exacerbated but not caused by work exposures.Occupational asthma can be caused by different mechanisms (Figure 1).  It is most often due to a workplace sensitizer, which is a high- or low-molecular weight agent that causes asthma from an immunologic response. Asthma symptoms do not occur on the first exposure. Instead, they require a period ranging from days to years for sensitization. Once sensitized, subsequent exposures, even to very low levels of exposure, will trigger asthma. When this response is due to high-molecular weight sensitizers, which are typically proteins or glycoproteins, it is associated with specific IgE antibodies. In addition, specific IgE-antibodies are also associated with the response to some low molecular-weight sensitizers (chemical sensitizers) such as complex platinum salts and other metal salts. However, for most low-molecular weight sensitizers, the immune mechanism is unclear.